Content-Based Filtering pada Sistem Rekomendasi Buku Informatika - Ridhwanullah, Dziky; Kumarahadi, Yovita Kinanti; Raharja, Bayu Dwi (STMIK Sinar Nusantara, 2024)
There are changes taking place in Indonesia's educational system, particularly in universities. The learning approach used in the transformation program is student-centered. A firm foundation in literacy is required for the application of this learning. A library is one of the amenities that students require. The library is an ideal resource for pupils to enhance their critical thinking skills. It's not always simple to find books in the library, though. Students could find it challenging to locate the books they seek because there are so many collections already in existence. One method for doing book searches is through the use of a recommendation system. Using content based filtering is one recommendation system algorithm. This study suggests a content based filtering algorithm-based book recommendation system to facilitate students' search for informatics book titles. TF-IDF and Cosine Similarity are used in a similarity search to find phrases and assign weights to them. The content-based filtering algorithm's research findings might suggest books depending on user-specified parameters. 90% accuracy is the average for this method.Keywords: recommendation system, content based filtering, TF-IDF, Cosime Similarity